Small scale energy harvesting for use with an electronic door strike - Cechmanek, Grant (University of Waterloo, 2016)
Smart or connected devices are becoming more and more prevalent in modern society. These devices typically consist of miniature sensors and actuators to automate and control common daily activities. The spread of these devices comes with the need to supply power to these devices. A first approach is often to include a battery to allow for remote operation. The immediate drawback to this approach is the eventual need to either replace or recharge this battery. A power generation system that both compact and portable is desired. Any such system which can operate by extracting ambient energy from the environment would see applications in many common devices ranging from common calculators, to industrial equipment health monitoring systems. One common device that is experiencing the transition from a purely mechanical to smart device is the standard door lock. Keyless access is gaining prevalence in both office buildings and private residences as it allows for greater convenience and added security measures. These benefits come at the cost of electrical energy consumption, which is presently being primarily supplied through direct wire routing from the building's main grid. An electronic locking mechanism that is fully physically autonomous and energy independent would be advantageous. In this work the application of energy harvesting methods as they relate to an electronic door strike, or E-strike, are investigated. Multiple different common ambient energy sources are identified and their expected power densities quantified. These range from 9 μW to 7W depending on the source. From these sources human action is identified as possessing the highest power density, and also being the most reliably available source. A system to model the energy flow through an E-strike is derived. This model accounts the maximum available energy, harvesting efficiency, required power draw, and storage capabilities. An E-strike prototype is constructed and experiments are conducted to validate the proposed model. The proposed design provides and energy density of 4.25mJ/cm3. The overarching goal is to identify under what operating conditions an E-strike will be able to operate indefinitely, without the need to add physical power lines or replace batteries. A single combined parameter, the Activation-per-input value is defined and identified as the key characteristic that determines which environments will be suitable for an energy harvesting E-strike. Results of these experiments demonstrate that an E-strike can operate indefinitely with an Activation-per-Input ratio of 0.1 or below.
Keywords: energy harvesting; energy scavenging